Community Filter Based EB Plan Recommendation System - C.Bhanu Prakash Reddy, Ms. M. ELAKIYA, Ms.D.Mahalakshmi (International Journal of Advanced Science and Technology, 2020)
Electricity Billing System is a software program-based totally application developed in java programming language. At the same time as now not power we have a tendency to can’t able to live to tell the tale. Because the population increase is circulated on developing the intake of the strength is developing. Currently an afternoon’s the net internet application is advanced based totally basically upon the range of power fed on the prices may additionally additionally moreover get generated. The rate of the charged will created through net portal of the EB workplace. The SQL is employed that creates a information set it includes the facts of the customers but it's the restrictions it's far one set of column to go back decrease lower back regular with cluster. But many of the new device the SQL has the horizontal row set of records it shops a handful of units of information of the customer. They can have a glance at the expenses based totally upon the consumption. It what is extra created Associate in Nursing intimation as soon as the use of the electricity consumption reaches the most range. As a result, be privy to exploitation the energy during a minimum vary. Within the horizontal set of statistics, it makes use of the PIVOT technique to shape the technique some of faster and accurate.